Entrepreneurial Characteristics and Competence as the Predictors of Village-Owned Enterprises (BUMDesa) Governance - Abdul Muis; Bambang Dwi Suseno; Malik Fatoni; Mulyadi Mulyadi; Nor Shamshiza (Relevance: Journal of Management and Business, 2022)
This study aims to answer why BUMDesa is always entangled with problems and difficulties to develop and governance. The approach applied in this research was correlational quantitative. The study population included 326 BUMDesa in Pandeglang Regency, Banten Province spread over 32 sub-districts. The samples were selected through purposive sampling technique. The samples were 9 BUMDesa which had run businesses with fairly good activities in 2 sub-districts with coastal tourism characteristics, namely Labuan and Panimbang. Pandeglang sub-district as the capital of Pandeglang Regency, with trade and service characteristics, was also involved. In accordance with the developed hypothesis, the analysis of inferential statistical data was assessed by using the SmartPLS (Partial Least Square) software starting from the measurement model (outer model), model structure (inner model) and hypothesis test. Based on the results of test towards five hypotheses, it was shown that Village Fund had no significant effect on Competence, Village Fund had a significant effect on BUMDes, Entrepreneurial characteristics had an effect on the Competence in BUMDesa governance, Entrepreneurial characteristics had a positive and significant effect on BUMDesa and Competence had a significant effect on BUMDesa governance. Thus, this study provided an evidence that problematic national BUMDesa governance was confirmed in 9 BUMDesa in 3 sub-districts in Pandeglang Regency.